Siderophore-Producing Bacteria from a Sand Dune Ecosystem and the Effect of Sodium Benzoate on Siderophore Production by a Potential Isolate - Teja Gaonkar; Pramoda Kumar Nayak; Sandeep Garg; Saroj Bhosle (The Scientific World Journal)
Bioremediation in natural ecosystems is dependent upon the availability of micronutrients and cofactors, of which iron is one of the essential elements. Under aerobic and alkaline conditions, iron oxidizes to Fe+3 creating iron deficiency. To acquire this essential growth-limiting nutrient, bacteria produce low-molecular-weight, high-affinity iron chelators termed siderophores. In this study, siderophore-producing bacteria from rhizosphere and nonrhizosphere areas of coastal sand dunes were isolated using a culture-dependent approach and were assigned to 8 different genera with the predominance of Bacillus sp. Studies on the ability of these isolates to grow on sodium benzoate revealed that a pigmented bacterial culture TMR2.13 identified as Pseudomonas aeruginosa showed growth on mineral salts medium (MSM) with 2% of sodium benzoate and produced a yellowish fluorescent siderophore identified as pyoverdine. This was inhibited above 54 μM of added iron in MSM with glucose without affecting growth, while, in presence of sodium benzoate, siderophore was produced even up to the presence of 108 μM of added iron. Increase in the requirement of iron for metabolism of aromatic compounds in ecosystems where the nutrient deficiencies occur naturally would be one of the regulating factors for the bioremediation process.